Die älteren Urkunden des Domkapitels zu Aquileia und des Klosters Beligna (bis 1250) - Härtel, Reinhard (Verlag der Österreichischen Akademie der Wissenschaften, 2025)
Half of the texts of this edition were previously completely unknown, and many other texts have now been edited verbatim for the first time, or are now available due to a significantly better textual basis than before, or they now appear with a corrected date. Several studies round off the text edition: a presentation of previous research, as well as an investigation into the history of this archive, and in addition, there are special studies on individual documents and groups of documents. Not only the place and personal names appearing in the texts are indexed and identified, but the peculiarities of the legal phraseology of the Middle Ages are also listed. Die Edition enthält zur Hälfte bisher völlig unbekannte Texte und darüber hinaus zahlreiche bisher noch nie im Wortlaut oder nur aufgrund mangelhafter Textgrundlagen bzw. unter falschem Datum edierte Stücke. Detailstudien zur bisherigen Forschung, zur Archivgeschichte und zu einzelnen Urkunden oder Urkundengruppen runden die Edition ab. Die in den Texten vorkommenden Orts- und Personennamen werden ebenso durch Register erschlossen wie die Eigentümlichkeiten der mittelalterlichen Rechtssprache in ihrer Phrasenbildung insgesamt.